Judeus Ashkenazim e Anussim: memórias e identidades da Comunidade Judaica em Ponta Grossa – PR, 1894 - 2021 - ARAÚJO, ROSÂNGELA DE ARRUDA (2021)
The present study seeks to contribute to the Jewish historiographical record in the city of Ponta Grossa-PR, through interviews based on Oral History as a resource for accessing the memory collections of Ashkenazim and Anussim Jewish descendants. This is a qualitative research that involves an interpretative approach based on shared memories. The temporal delimitation comprises the period from 1894, referring to the arrival of the first Ashkenazim Jewish families in migratory waves to 1966, with the arrival of the last family of expatriate Jews who survived the Nazi Holocaust and a descendant of Anusim Jews, coming with a Christian- new, in the search for their Jewish roots since 1998, called Bnei Anusim - children of the forced, who in 2021 consolidate the Bnei Anusim Association. For the bibliographical basis, classic works in Jewish studies were used: Novinsky (1972, 2015), Carneiro (2013), Vainfas (2013), among others. To promote historiographic conceptualizations, theoretical assumptions are anchored in Lesser (1995), Koifman (2012), Lewin (2013) and Soares (2012). The concepts of memories and identities are supported in Nora (1993), Halbwachs (1990), Sarlo (2007), Pollak (1992) and Hall (1992). The Oral History combined with the History of the Present Time is based on Alberti (2013), Ferreira and Amado (2006) and Dosse (2001), being used as a methodology to approach aspects that are insufficient in the documentation. The study provides an opportunity to listen to those who bring in their memory’s experiences lived and inherited from their ancestors and which are inserted in the experiences of each of the historical subjects. The guiding objectives are to know when they arrived and why they chose the city of Ponta Grossa, register how their adaptations, sociability and formation of the organized community were, and understand the elements and means for maintaining the Jewish identity. In the case of the Anussim Jews we registered how process of returning Jewish roots took place, since the forced conversions to Christianity are secular and that, in order to understand the process of formation of memories and maintenance of identities, it is necessary to establish relationship between the Jewish womb and the understanding of what it is "to be a Jew". Through individual and collective memory was possible to record the beginning, heyday and end of the Ashkenazim Jewish community in Ponta Grossa, making it possible to inventory the process of union for the foundation of the Anussim Association today.